The Influence of Herd Mentality and Organizational Culture on Employee Performance in the Area Collection Unit of Bank BTN KC Cikarang - Yosua Permata Marpaung; Fa’uzobihi Fa’uzobihi; Partimah Partimah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the influence of herd mentality and organizational culture on employee performance at the BTN Bank Area Collection Unit, Cikarang Branch. Herd mentality is an individual's tendency to follow group thought patterns or actions without rational consideration, while organizational culture reflects shared values and norms in the work environment. Employee performance is measured based on quality, quantity, punctuality, and responsibility for work. The research method used is quantitative with a survey approach by distributing questionnaires to 50 respondents. Data were analyzed using multiple linear regression to determine the simultaneous and partial effects of independent variables on dependent variables. These findings provide an influence for management to create a positive work culture and understand social dynamics over time as an effort to improve performance.